Analisis Pertimbangan Hakim Praperadilan Putusan 33/Pid.Prap/2020/PN.JKT.SEL Tentang Penetapan Tersangka Tidak Sah dalam Keadilan Kepastian Hukum (RechtJiva, 2024)
Law must live in society, serving more than a guideline or a clue giving guidance to dormant activities in society. Therefore, pretrial exists as a means of control. Pretrial in Indonesia is basically regulated in Articles 77 to Article 83 of the Law of the Republic of Indonesia Number 8 of 1981 concerning the Criminal Procedure Code, where the object of pretrial was expanded by Constitutional Court Decision Number 21/PUU-XII/2014. There is an interesting thing in the decision of the South Jakarta District Court judge who examined and adjudicated the pretrial case in the South Jakarta District Court decision Number 33/Pid.Prap/2020/PN.Jkt.Sel.. This research was carried out in a normative juridical manner, using a statue approach and case approach. This research aims to analyze legal regulations and protection regarding pretrial in Indonesia, and to analyze the judge's considerations in the pretrial decision of the South Jakarta District Court Number 33/Pid.Prap/2020/PN.Jkt.Sel.. The results of this research show that the judge's considerations in South Jakarta District Court decision Number 33/Pid.Prap/2020/PN.Jkt.Sel. does not contain the aim of the law itself, in this case, justice and legal certainty, this is due to limited pretrial regulations.